Antrax in Primorsky Territory (1919–2020). Communication 1. Historical Records and Characteristics of Stationary Potentially Hazardous as Regards Antrax Areas - Z. F. Dugarzhapova; M. A. Ivacheva; M. V. Chesnokova; E. V. Kravets; E. A. Reshetnyak; D. Yu. Kuzin; A. A. Umanets; T. N. Detkovskaya; S. V. Balakhonov (Проблемы особо опасных инфекций, 2021)
The aim of the study was to analyze the state of stationary potentially hazardous areas as regards anthrax in the Primorsky Territory and update the Cadastre of stationary potentially hazardous as regards anthrax areas (SPHA) of the Russian Federation (2005).Materials and methods. The collection and survey of accounting and reporting documents, archival and informational materials, records on anthrax from veterinary institutions, Rospotrebnadzor, municipalities by the 72 registered anthrax SPHA of the Primorsky Territory have been carried out. The reference book of the Russian Soviet Federative Socialist Republic’s settlements endemic for anthrax (1976), the Cadastre of the stationary potentially hazardous as regards anthrax areas in the Russian Federation (2005) were used.Results and discussion. The description of anthrax cases in the Primorsky Territory goes back to 1894, the official registration of the disease – since 1919. The last cases of the disease in farm animals and population were noted in Kavalerovsky and Oktyabrsky districts in 1979. When updating the SPHA (2005), information on 82 dormant sites of the Territory in 22 municipal and six urban districts was clarified. In six districts of the Territory, anthrax was not officially registered. Most of the SPHAs are centered on the Khanka plain, where the network of transport routes, the largest number of livestock and population are concentrated. The data on the number of sick animals and people over a period of 1919–1929 have not survived, and in the period between 1980 and 2020 anthrax was not reported in the region. 173 animals and 34 humans were diagnosed with anthrax in 1929–1979 in Primorye. High epizootic activity was noted in the period of 1919–1941. In the Asian part of the Russian Federation, Primorsky Territory belongs to the regions under a mild epizootic and epidemiological disadvantage as regards anthrax. Monitoring of anthrax has shown that the persistence of the pathogen in the soils of ten districts of the Territory could be facilitated by the absence of soil toxicity (86,8 %) and an average nutritional value (23,5 %) in relation to the anthrax microbe.